2012
DOI: 10.1016/j.resuscitation.2012.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal intubation versus supraglottic airway insertion in out-of-hospital cardiac arrest

Abstract: Objective To simplify airway management and minimize cardiopulmonary resuscitation (CPR) chest compression interruptions, some emergency medical services (EMS) practitioners utilize supraglottic airway (SGA) devices instead of endotracheal intubation (ETI) as the primary airway adjunct in out-of-hospital cardiac arrest (OHCA). We compared the outcomes of patients receiving ETI with those receiving SGA following OHCA. Methods We performed a secondary analysis of data from the multicenter Resuscitation Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 34 publications
(37 reference statements)
7
92
1
4
Order By: Relevance
“…Recent studies, however, have reported worse outcomes for out-of-hospital cardiac arrest patients managed with EADs compared to intubation, and it has been suggested that this may be attributable to neck vessel compression. 1,2,10 While the results of our small study cannot fully refute this claim, they do suggest that the compressive effect on cerebral arterial blood flow may not entirely account for the noted differences in outcome.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Recent studies, however, have reported worse outcomes for out-of-hospital cardiac arrest patients managed with EADs compared to intubation, and it has been suggested that this may be attributable to neck vessel compression. 1,2,10 While the results of our small study cannot fully refute this claim, they do suggest that the compressive effect on cerebral arterial blood flow may not entirely account for the noted differences in outcome.…”
Section: Discussioncontrasting
confidence: 61%
“…1 Most EADs use an inflatable cuff in the hypopharynx to prevent airflow into the esophagus and to direct airflow into the trachea and lungs (see Figure 1). There exists a theoretical concern that the inflated cuffs on these devices may cause compression of the arteries in the neck that supply the brain.…”
Section: Discussionmentioning
confidence: 99%
“…3 Despite robust systems of care for patients with trauma and rapidly evolving systems of care for patients with ST-segment-elevation myocardial infarction (STEMI) and stroke, the majority of communities do not achieve optimal survival after OHCA because of large discrepancies in resuscitation-related processes of care. [4][5][6] As a result, survival to hospital discharge varies significantly both across different regions and by presenting rhythm. 7,8 Survival increases significantly if the OHCA is quickly recognized and responded to with prompt activation of 9-1-1, bystander-initiated cardiopulmonary resuscitation (CPR), bystander and/or basic first responder application of an automated external defibrillator (AED) before arrival of other emergency medical services (EMS) providers on scene, advanced life support, and postresuscitation care.…”
mentioning
confidence: 99%
“…In the ensuing discussion, it will be delineated how several under-recognized confounding variables have a major impact on the performance of this skill and even related outcomes. These variables include non-intuitive factors, such as how the EMS providers are deployed or how they have been trained to ventilate [32][33][34][35][36][37][38][39][40][41][42][43][44]. These concepts and how they relate to the success of prehospital ETI for the critically ill and injured will be addressed in the rest of this article.…”
Section: Introductionmentioning
confidence: 99%